2011
DOI: 10.1177/193758671100500105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Private Room with Multiple-Bed Ward Neonatal Intensive Care Unit Environments

Abstract: Objective: This study determined whether a private room or open ward design better met optimal environmental conditions for a neonatal intensive care unit with regard to sound level, light level, temperature and humidity. Background: Multiple-bed designs for hospital neonatal intensive care units were the standard until recently. Now, private room designs promise to provide better conditions for neonate development and patient care quality. Methods: The study compared an eight-bed open ward design with a priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 12 publications
(11 reference statements)
2
25
0
1
Order By: Relevance
“…[7][8][9] Modern NICU design incorporates acoustical architectural design elements to reduce sound exposure. Single family rooms (SFR) and open-pod rooms are quieter than open bay rooms, 10,11 but the impact of patient acuity and the relative contribution of individual environmental factors has not been well studied. Benefits of SFR design include decreased stress and improved long-term outcomes.…”
mentioning
confidence: 99%
“…[7][8][9] Modern NICU design incorporates acoustical architectural design elements to reduce sound exposure. Single family rooms (SFR) and open-pod rooms are quieter than open bay rooms, 10,11 but the impact of patient acuity and the relative contribution of individual environmental factors has not been well studied. Benefits of SFR design include decreased stress and improved long-term outcomes.…”
mentioning
confidence: 99%
“…The noise level is higher in multibed than single-bed rooms (8,10,18), and noise increases subjective stress, annoyance, sympathetic nervous system activation (19), and sleep disruption (8). It has been proved that sleep disruption and the consequent deprivation are associated with an increase in delirium prevalence (20) and confirming that association, the use of ear plugs during the night decreases the delirium prevalence in ICU patients (21).…”
Section: Hypotheses For the Difference In Delirium Prevalencementioning
confidence: 87%
“…A previous study showed that during the day, the light level in single-bed rooms is higher than in multibed rooms due to a higher area of windows (10). Also in the present study, patients admitted in single-bed or multibed rooms were exposed to natural light; however, the patients in single-bed rooms were exposed to an increased number of windows and to a more controllable lighting (more intense light during the day and less during the night).…”
Section: Hypotheses For the Difference In Delirium Prevalencementioning
confidence: 96%
See 1 more Smart Citation
“…(3) Unit net to gross ratios and the mean net to gross ratio for each unit category vary widely in US hospitals (Allison and Hamilton, 2008). (4) Units with private rooms allow for a patient care environment that can be maintained within a smaller range of variation nearer optimal environmental conditions (Van Enk & Steinberg, 2011).…”
Section: Studies Describing Unit Layout and Designmentioning
confidence: 99%